2019
DOI: 10.1111/avj.12778
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of Australian veterinarians and their perceptions and experiences related to online pet health information

Abstract: Objective Investigate Australian veterinarians’ perceptions of clients’ use of the internet to find pet health information. Methods An anonymous online survey was distributed using social media, e‐newsletters and veterinary magazines. Results A total of 85 complete responses were obtained from Australian veterinarians. Most (80%) reported believing that > 80% of their clients have access to the internet at home or work, but 68% thought that the majority of their clients do not understand what they read online.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…A prior study of Australian veterinarians found that the majority (76.5%) of veterinarians thought that between 41 and 80% of pet owners used the internet for pet health information . However, this study found that 96.1% of pet owners use the internet for pet health information, suggesting that veterinarians might underestimate their clients' use of the internet for seeking pet health information.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A prior study of Australian veterinarians found that the majority (76.5%) of veterinarians thought that between 41 and 80% of pet owners used the internet for pet health information . However, this study found that 96.1% of pet owners use the internet for pet health information, suggesting that veterinarians might underestimate their clients' use of the internet for seeking pet health information.…”
Section: Discussionsupporting
confidence: 90%
“…Website security and privacy settings are important aspects to consider for both pet owners and veterinary staff . Yet, even when websites are secure, current, unbiased and accurate, there is still a risk for misinterpretations by the user …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second pilot study looked at responses from 85 veterinarians about their perceptions of their clients’ and owners’ use of the internet and whether they could understand the information that they found …”
Section: Education Ethics and Welfarementioning
confidence: 99%
“…Our second pilot study looked at responses from 85 veterinarians about their perceptions of their clients' and owners' use of the internet and whether they could understand the information that they found. 2 Most respondents were young women. Just over 78% of respondents considered that less than 40% of their clients understood what they had read online, although 72% thought that more than 60% of their clients trusted what they read online.…”
mentioning
confidence: 99%